Anatomía vegetativa de Lophophytum mirabile subsp. bolivianum (Balanophoraceae) y efecto de su parasitismo en la anatomía de las raíces de su hospedante Anadenanthera colubrina var. cebil - González, Ana María (2016)
The objectives of this work were to study the structure of the vegetative body of Lophophytummirabile subsp. bolivianum; analyze the change on roots of Anadenanthera colubrina when they areinfected by this parasitic plant, and identify the anatomical changes produced by that parasitism.Lophophytum mirabile plants are formed by a spheroidal- narrower underground vegetative body ortuber, externally has a dark warty surface, lacks epidermis, stomata or trichomes. The central matrixof tuber consists of reserving parenchyma and vascular bundles. Parasitic cells located at the level ofroot cambium initiates the tubers formation, externally visible as exophyte . On the infected root ofA. colubrina, the identity of radial and axial growth of the secondary system it is lost. This leads to theformation of xylem loops that affecting the xylem transport and root development, which stopsgrowing in length and develops a woody gall. Infection of L. mirabile causes profound anatomicalchanges in developing timber of A. colubrina, which favor the successful of the parasite.